Prevalence of human papillomavirus genotypes and precancerous cervical lesions in a screening population in the Republic of Korea, 2014–2016 - Ouh, Yung-Taek; Min, Kyung-Jin; Cho, Hyun Woong; Ki, Moran; Oh, Jin-Kyoung; Shin, Sang Yop; Hong, Jin Hwa; Lee, Jae-Kwan (Journal of gynecologic oncology, 2018)
Knowledge regarding the prevalence and distribution of human papillomavirus (HPV) genotyping in healthy women is important in establishing strategies for cervical cancer screening and HPV vaccination. A total of 18,170 women who visited a Korean Medical Institute for health check-ups were recruited retrospectively; they underwent HPV genotyping and conventional cervical cytology. An HPV DNA test was performed using the Anyplex™ II HPV 28 detection system (Seegene) or HPV Liquid Bead Microarray (Osang Healthcare). The distribution of HPV genotypes was assessed according to cervical cytology and age. HPV was detected in 3,037 (16.71%) of the 18,170 women enrolled, and 2,268 (12.48%) were positive for high-risk (HR) HPV. In total, HPV 53 (9.69% of all detected HPV viruses) was the most common type; HPV 58 (7.90%) and 52 (7.81%) were also common. HPV 54 (6.99%) was common in low-risk subjects. Overall and in the normal cytology group, the most common HPV genotype was HPV 53, whereas HPV 58 was more common in women who had atypical squamous cells of undetermined significance or low-grade squamous intraepithelial neoplasia cervical cytology. In addition, HPV 16 was the most common type in cases with high-grade squamous intraepithelial neoplasia (HSIL)/atypical squamous cells-cannot exclude HSIL. Among women with normal cytology, 76 of 231 (32.9%) women under 24 years of age were positive for HR HPV, whereas 84 of 852 (9.9%) women aged 55-59 years were positive. HPV 53 was the most prevalent genotype in healthy women. Distribution of HPV genotypes varied with cervical cytology and age. Our study provides important baseline data for the recently implemented national HPV vaccination program.